Functional and speech outcomes of superiorly based flap pharyngoplasty combined with radical intravelar veloplasty - Abdelrahman E. M. Ezzat; Rana A Khalifa; Mabrouk M Akel; Hanna M El-Shenawy (Wolters Kluwer Medknow Publications, 2015)
Objective: The aim of this study was to evaluate functional and speech outcomes of superiorly based pharyngeal flap (SBF) pharyngoplasty combined with radical intravelar veloplasty (RIVVP) for the management of velopharyngeal insufficiency (VPI) following surgically repaired cleft palate. Design: A case series with chart review. The study was conducted in academic tertiary care medical centre. Patients and Methods: Fifteen patients with VPIs following surgically repaired cleft palate were managed between May 2011 and August 2014, with SBF pharyngoplasty combined with RIVVP. Results: We found that the speech defects improved by a success rate of 93.4%; the VP function became normal (circular pattern of closure) in 80% of patients and the postoperative overall success rate of VP competence grades was 93.4%. Moreover, we found that the overall incidence of complications were 33.3%. Conclusion: By doing SBF pharyngoplasty combined with RIVVP the surgical procedure was satisfactory in both functional and speech outcomes.